SENTIMENTS, CONDUCT, AND TRUST IN THE LABORATORY. Issue 1 (14th June 2017) - Smith, Vernon L.; Wilson, Bart J.
Abstract: In this essay we provide a brief account and interpretation of The Theory of Moral Sentiments showing that it departs fundamentally from contemporary patterns of thought in economics that are believed to govern individual behavior in small groups, and contains strong testable propositions governing the expression of that behavior. We also state a formal representation of the model for individual choice of action, apply the propositions to the prediction of actions in trust games, report two experiments testing these predictions, and interpret the results in terms directly related to the model. In short, we argue that the system of sociability developed by Adam Smith provides a coherent non-utilitarian model that is consistent with the pattern of results in trust games, and leads to testable new predictions, some of which we test.